Histoire du chien de Brisquet / The Story of Brisquet's Dog - Nodier, Charles, 1780-1844; Wooff, Michael (Salt Lake City, UT : Project Gutenberg, 2017)
"Histoire du chien de Brisquet / The Story of Brisquet's Dog" by Charles Nodier is a tale written in the early 19th century that weaves together elements of folklore and moral storytelling. This narrative revolves around a humble woodcutter named Brisquet and his family's tribulations during a harsh winter when wolves threaten their safety. The book highlights themes of loyalty, family, and the perils of neglect in the form of a poignant fable. The story unfolds in a quaint forest setting where Brisquet lives with his wife, Brisquette, and their two young children, Biscotin and Biscotine. They also have a devoted dog named Bichonne. One day, despite Brisquet's warnings to keep the children and Bichonne safely at home while wolves roam the area, they venture out. Tragically, Bichonne sacrifices herself to save the children from a wolf attack, demonstrating unparalleled loyalty. Although Brisquet manages to kill the wolf, he arrives too late to save Bichonne. The family mourns their loss, and Brisquet buries the dog with a marker, which leads to the popular proverb about the unfortunate fate of Brisquet$1 (Bs beloved canine. The story evokes deep emotions about love, loss, and the bonds between humans and animals. (This is an automatically generated summary.)s
Release date is 2017-09-22
Produced by Michael Wooff
Keywords: Dogs -- Juvenile fiction